AN ANALYSIS OF SYMBOLIC MEANING FOUND IN ROBERT FROST’S POEMS “A BOY’S WILL” - Yohana Chindy Hati Wigia Rindarti (Faculty of Education and Teachers Training, 2018)
As one genres of literature, poetry has poetic values that bring meaning, music, and emotion on its words. Symbols as one of the poetic values are usually used as the central to the way our minds and words function. Moreover, symbolic meaning involves the developments of students’ critical thinking and linguistic skills. The objectives of the research are; 1) to know the kinds of symbolic meaning and 2) to know the dominant symbolic meaning found in Robert Frost’s Poems “A Boy’s Will”. This research deals with semantic approach. It belongs to qualitative research and descriptive qualitative as research design. The method of collecting data is closed reading and documentation. The writer analyze the symbolic meaning using the theory by Timpane and Watts (2001) that has three parts; “A” referred to the symbol itself; “B” is what the symbol stand for; and “C” is the meaning of the symbol. Furthermore, the writer also used Shamisa’s theory (2004) to classify kinds of symbolic meaning. This theory has two kinds of symbolic meanings, arbitrary symbol and personal symbol. The result of the research reveals that the total number of symbolic meaning is 30 data. They consist of 6 arbitrary symbols or 20% of total findings and 24 personal symbols or 80% of total findings. Thus, the dominant symbolic meaning found in Robert Frost’s poems “A Boy’s Will” is personal symbols. The implication of this research is to improve students’ understanding on poems and help them to grasp the entire contexts of the poem.